Spectrophotometric Evaluation of Tooth Color in Children with Mixed Dentition - Şeyma Eslem Veske; Şerife Özalp (Cumhuriyet University, 2018)
ABSTRACT Objective In this study, the aim is to evaluate the shade of colors of the permanent maxillary central incisor, deciduous canine, deciduous first molar, deciduous second molar and permanent first molar teeth in individuals in mixed dentition stage using Vita Classic and Vitapan 3D Master scale, according to the L*, a*, b* color system.  Materials and Methods  Our study was performed on a total of 57 child patients between 7-12 years old. Color shade measurements were performed using VITA Easyshade Compact (Vita Zahnfabrik, Germany) spectrophotometry device; and CIE L*, a*, b* values according the Vita Classic and Vitapan 3D Master scale were recorded. Results In light of the obtained data, it was found that the L* value of the permanent first molar was the lowest, the L* value of the deciduous canine was the highest (p<0.001). The a* value of the central incisor was the lowest, whereas the a* value of the permanent first molar was the highest (p<0.001). According to the data, when the b* values were compared, a statistically significant difference was detected only between the central incisor and deciduous first molar teeth (p=0.005).                      Conclusion It was found that in individuals at the mixed dentition stage, according to the Vita Classic scale, B2 tones were found more frequently in permanent teeth   whereas A2 tones were more common in the deciduous teeth. C2 and D3 tones were not detected in both groups.